Early weaning is beneficial to prevent atopic dermatitis occurrence in young children. Issue 6 (4th March 2016) - Turati, F.; Bertuccio, P.; Galeone, C.; Pelucchi, C.; Naldi, L.; Bach, J.‐F.; La Vecchia, C.; Chatenoud, L.; ,
Abstract: Background: Epidemiological data on infant feeding practices and allergic diseases are controversial. The purpose of this study was to explore the association of early weaning with the occurrence of atopic dermatitis (AD). Methods: We conducted a matched case–control study on incident physician‐diagnosed AD in early childhood including 451 cases and 451 controls. Data on several factors, including feeding practices, were collected through an interviewer‐administered questionnaire. Odds ratios (OR) and the corresponding 95% confidence intervals (CIs) were estimated through logistic regression models, conditioned on study center, age, sex, and period of interview, and adjusted for potential confounders. Results: Early weaning, defined as the introduction of solid foods at 4 or 5 months of age, was inversely related to the risk of AD, with children weaned at 4 months having lower AD risk (OR = 0.41, 95% CI, 0.20–0.87) compared to those exclusively breastfed. Similar results were observed for weaning started at 5 months of age (OR = 0.39, 95% CI, 0.18–0.83). This association persisted when children with and without family history of allergy were considered separately. Prolonged partial breastfeeding (breastmilk plus milk formulas) was not associated with AD. Consistently, the introduction of a high number of different solid foods reduced the risk of AD ( P trend = 0.02 at 4 months of age and P trend = 0.04 at 5 months). Conclusion: Our data provide evidence against the preventing role of prolonged exclusive (but not partial) breastfeeding in AD occurrence and confirm recent results indicating a beneficial role of early weaning in AD.